Insects as food and medicine: a sustainable solution for global health and environmental challenges - Aidoo, Owusu Fordjour; Osei-Owusu, Jonathan; Asante, Kwasi; Dofuor, Aboagye Kwarteng; Boateng, Belinda Obenewa; Debrah, Shadrack Kwaku; Ninsin, Kodwo Dadzie; Siddiqui, Shahida Anusha; Chia, Shaphan Yong (Frontiers in Nutrition, 2023)
Insects are a significant source of food for millions of people worldwide. Since ancient times, insects in medicine have been contributing to the treatment of diseases in humans and animals. Compared to conventional animal farming, the production of insects for food and feed generates significantly less greenhouse gas emissions and uses considerably less land. Edible insects provide many ecosystem services, including pollination, environmental health monitoring, and the decomposition of organic waste materials. Some wild edible insects are pests of cash crops. Thus, harvesting and consuming edible insect pests as food and utilizing them for therapeutic purposes could be significant progress in the biological control of insect pests. Our review discusses the contribution of edible insects to food and nutritional security. It highlights therapeutic uses of insects and recommends ways to ensure a sustainable insect diet. We stress that the design and implementation of guidelines for producing, harvesting, processing, and consuming edible insects must be prioritized to ensure safe and sustainable use.